y = 1 + a1/(x-a1) + a2/((x-a1)(x-a2)) + a3/((x-a1)(x-a2)(x-a3))
then dy/dx = (y/x) (a_{1}/(a_{1} - x) + a_{2}/(a_{2} - x) + a_{2}/(a_{2} - x))
y = 1 + a1/(x-a1) + a2/((x-a1)(x-a2)) + a3/((x-a1)(x-a2)(x-a3))
then dy/dx = (y/x) (a_{1}/(a_{1} - x) + a_{2}/(a_{2} - x) + a_{2}/(a_{2} - x))
Last edited by stapel; 07-23-2017 at 03:57 PM. Reason: Copying question from subject line into post.
You'll have to show us how you got there. Where did a3 go?
"Unique Answers Don't Care How You Find Them." - Many may have said it, but I hear it most from me.
Bookmarks